Palladium-Catalyzed Ring-Opening Coupling of Cyclobutenols with Aryl Halides - Matsuda, Takanori; Matsumoto, Takeshi; Murakami, Akira (Synlett, 2018)
A palladium(0)-catalyzed ring-opening cross-coupling reaction between tert-cyclobutenols and aryl halides produces γ-arylated β,γ-unsaturated ketones. In the case of aryl halides bearing functional groups at the ortho position, the resulting ring-opened ketones undergo intramolecular condensation to afford bicyclic aromatic compounds.
Keywords: palladium; cyclobutenols; arylation; ring opening; ketones; cross-coupling; condensation; homogeneous catalysis